Intraductal papillary neoplasm of the bile duct presenting as multiple pedunculated polyps in the common bile duct at the cystic duct confluence: A case report. (July 2021) - Usui, Asami; Ohta, Yoshito; Nishimori, Takanori; Kuroda, Hiroaki; Shinohara, Yasushi; Sakamoto, Akio
Abstract: Introduction and importance: Intraductal papillary neoplasm of the bile duct (IPNB) is known as a precancerous lesion. We herein report a case of IPNB containing adenocarcinoma presenting as multiple pedunculated polyps of the common bile duct with lateral spread of dysplasia at its base. Case presentation: A 76-year-old male was admitted to our institution for hematemesis and found to have gastric cancer. Preoperative examinations revealed a tumor in the common bile duct. The patient underwent distal gastrectomy along with bile duct resection. Frozen sections of the resected specimen were checked during the operation and revealed adenocarcinoma. Proximal and distal bile duct margins were also checked and shown to be free of cancer as well as dysplasia. On the resected bile duct, a polypoid lobulated lesion with two heads of 2 cm each growing from a single stalk was located in the common bile duct near the cystic duct confluence, with another 2 cm polypoid lesion on a stalk nearby. The two lesions appeared to be positioned in the common bile duct and cystic duct in a discontinuous manner, but a continuous area of high-grade dysplasia was found to spread at the base of both lesions. Based on the histopathological findings, the tumor was diagnosed as pancreatobiliary type IPNB with carcinoma. Clinical discussion: IPNB presents a favorable prognosis after surgical resection but is also known to recur in the residual bile ducts. Surgical resection of the recognizable area of pathology would be the effective treatment option for IPNB with lateral superficial spread and multiple lesions. Conclusion: We surgically removed an IPNB presenting as multiple pedunculated polyps with lateral spread of dysplasia at its base. Careful postoperative follow up is imperative in IPNB, since recurrence may occur in the remnant bile ducts. Highlights: Intraductal papillary neoplasm of the bile duct (IPNB) is known to be precancerous. Multiple lesions with lateral spread of dysplasia at its base as IPNB is uncommon. Complete surgical removal including dysplasia is necessary to avoid recurrence.